Environmental cognition and subjective well‐being: A study among middle‐aged and elderly residents in Nara Prefecture, Japan - Shota Takamine; Haruhiko Goto; Fuyumi Liu; Shu Yamamura (Japan Architectural Review, 2024)
Abstract Subjective well‐being has been attracting a considerable amount of attention. Urban planning is expected to play a significant role in improving subjective well‐being. This study focuses on neighborhood environmental cognition as a new intervention target of urban planning and aims to clarify its association with subjective well‐being. We conducted surveys using the element‐recall method to assess neighborhood environmental cognition and the Subjective Well‐being Inventory. Data were collected from 104 respondents over 50 years old living in suburban area of Nara Prefecture, Japan. The results revealed the following: The ability to recall many or diverse elements is positively correlated with subjective well‐being. However, the spatial distribution of the recalled elements was not correlated with subjective well‐being. The components of subjective well‐being, positive affect and negative affect, have different relationships with neighborhood environmental cognition. Further, sex affects the association between negative affect and neighborhood environmental cognition. The ability to recall the elements that are not meant for daily visits is positively correlated with subjective well‐being. These findings suggest that, in addition to making cities walkable, creating places that are easy to be recognized and recalled by residents is also important.